2018
DOI: 10.1016/j.jqsrt.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

A high-performance atmospheric radiation package: With applications to the radiative energy budgets of giant planets

Abstract: A High-performance Atmospheric Radiation Package (HARP) is developed for studying multiplescattering planetary atmospheres. HARP is an open-source program written in C++ that utilizes high-level data structure and parallel-computing algorithms. It is generic in three aspects. First, the construction of the model atmospheric profile is generic. The program can either take in an atmospheric profile or construct an adiabatic thermal and compositional profile, taking into account the clouds and latent heat release… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 35 publications
4
57
1
Order By: Relevance
“…Polar aerosols could also potentially explain the slightly warmer summer temperatures at the poles in the lower stratosphere seen the Voyager data . If this was due to solar heating, such changes would only be expected from the radiative-dynamical model of Conrath et al (1990) if radiative time constants were significantly shorter than even those of Li et al (2018) at stratospheric heights. This could potentially be caused by unaccounted presence of absorbing aerosols.…”
Section: Comparison To Visual/near-ir Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Polar aerosols could also potentially explain the slightly warmer summer temperatures at the poles in the lower stratosphere seen the Voyager data . If this was due to solar heating, such changes would only be expected from the radiative-dynamical model of Conrath et al (1990) if radiative time constants were significantly shorter than even those of Li et al (2018) at stratospheric heights. This could potentially be caused by unaccounted presence of absorbing aerosols.…”
Section: Comparison To Visual/near-ir Imagingmentioning
confidence: 99%
“…If variations in the seasonal albedo are related to changes in temperatures-whether through changes in condensation, subsidence, or convective stability-these temperature changes are not apparent in our upper tropospheric or stratospheric data. Li et al (2018) computed radiative time constants as short as a decade near the polar cloud tops (Sromovsky et al 2019), but the variation of cloud layer temperatures have yet to be measured. We have shown that radiative time constants at higher altitudes are either longer than expected or mixing can effectively dampen seasonal temperature changes.…”
Section: Comparison To Visual/near-ir Imagingmentioning
confidence: 99%
“…This result would be changed if a latitude-dependent absorbing aerosol were present (see Section 2.1), but the small magnitude of the temperature differences due to Uranus' small haze opacity should result in a weak annual-mean meridional circulation, with a low-latitude cell of rising motion between 10 − 30 ‱ in both hemispheres and subsidence at the equator. Li et al (2018) calculated updated estimates of the radiative heating/cooling rates, using modern estimates of temperature and hydrocarbon profiles. The rates at Uranus are much smaller than at Neptune because Uranus has the coldest atmosphere and the least stratospheric methane (and resulting photochemical products).…”
Section: Atmospheric Temperatures and Ortho/para-hmentioning
confidence: 99%
“…Furthermore, photolysis of CO and CO 2 can lead to secondary peaks of hydrocarbon production at higher altitudes . The spatial distribution of these stratospheric species control the local radiative balance (ethane and acetylene are excellent coolants, but their efficiency leads to a stratospheric energy crisis, e.g., Li et al 2018) and the condensation of thin stratospheric haze layers in the 0.1-30 mbar range (Rages et al 1991;Romani et al 1993;Moses and Poppe 2017;. Aerosol layers of water, benzene, CO 2 , acetylene, ethane and propane are just some of the various condensed layers that might be expected at these low temperatures.…”
Section: Stratospheric Circulation: Chemical Tracersmentioning
confidence: 99%
See 1 more Smart Citation